Effect of microprismatic eyeglasses on the character of binocular vision in children with strabismic amblyopia over treatment time (Ukrainian Journal of Ophthalmology, 2026)
Background: Strabismic children develop early motor and/or sensory complications (amblyopia, poor fixation of the eye, impaired fusion, and impaired binocular vision). The major goals of treatment for strabismic amblyopia are to remove strabismus, to improve the vision of the amblyopic eye, and to restore the binocular vision. Prisms and apparatus-based orthoptics techniques have been used for a long time for the treatment of impairments in binocular vision. In Ukraine, the technology for manufacture of spheroprismatic lenses designed as microprismatic combination eyeglasses was developed in 2009.Purpose: To investigate the effect of microprismatic glasses versus apparatus-based pleoptics-and-orthoptics techniques on the character of binocular vision in children with strabismic amblyopia.Materials and Methods:  One hundred and forty nine children with strabismic amblyopia aged 4 to 18 years were included into the study. Concomitant esotropia and exotropia were found in 77 children and 11 children, respectively, of the study group, versus 54 children and 7 children, respectively, of the control group. Six children (6.8%) of the study group, versus 13 children (21.3%) of the control group were those with partially accommodative strabismus, whereas the rest were those with non-accommodative strabismus. Children of the study group were treated with microprismatic glasses, whereas those of the control group were treated with apparatus-based techniques.Results: At 6 months, binocular single vision was obtained in 20 children (22.7%) of the study group versus only one child (3.0%) with low amblyopia of the control group. In addition, diplopia was present in 51 children (58.0%) of the study group versus 10 children (16.4%; 8 children (13.1%) at baseline) in the control group.Conclusion: The treatment proposed for strabismic amblyopia (a) requires no additional time, (b) has good outcomes, (c) is suitable for patients, and (c) is more efficacious than conventional apparatus-based pleoptics-and-orthoptics therapy.
Keywords: strabismic amblyopia; binocular character of vision; microprismatic glasses